1998
DOI: 10.1016/s0014-5793(98)00514-6
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of alkaline phosphatase containing phosphotyrosyl phosphatase activity from the bacterium Prevotella intermedia

Abstract: A novel alkaline phosphatase, designated PiALP, has been purified and characterized from Prevotella intermedia ATCC 25611, an anaerobe implicated in progressive periodontal disease. The enzyme was a homodimer of apparently identical subunits of M r 54 kDa. Thiol-reducing agents completely inhibited the purified enzyme. The enzyme was highly stable even at 80³C. It exhibited substantial activity against tyrosinephosphate-containing Raytide. The phosphatase activity was sensitive to orthovanadate and Zn P+ but h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
1
12
1
Order By: Relevance
“…Vanadate appeared to be a weak inhibitor of P. abyssi AP. This is not consistent with previous studies on other APs (1,6,21) and may be a result of the experimental conditions (pH 10.0, 70°C) or of an original catalytic mechanism. In contrast, thiol-reducing agents exhibited a strong inhibitory effect on AP activity.…”
Section: Discussioncontrasting
confidence: 99%
“…Vanadate appeared to be a weak inhibitor of P. abyssi AP. This is not consistent with previous studies on other APs (1,6,21) and may be a result of the experimental conditions (pH 10.0, 70°C) or of an original catalytic mechanism. In contrast, thiol-reducing agents exhibited a strong inhibitory effect on AP activity.…”
Section: Discussioncontrasting
confidence: 99%
“…Although the exact role of oral microbes in the etiology of periodontal disease remains unknown, they have been shown to produce a variety of potential virulence factors, including high phosphatase activity (38). To date, alkaline phosphatases (ALPases) of both P. intermedia and Porphyromonas gingivalis have been characterized (3,48). A neutral phosphatase gene was also isolated from the oral spirochete Treponema denticola, which is associated with chronic periodontal disease (14).…”
mentioning
confidence: 99%
“…For instance, small, acidic PTPases contain N-terminally located, highly conserved active sites (FVCXGN ICRSPXAEAXF) (20). Moreover, PiALP, an ALPase from P. intermedia, appeared to represent a new family of alkaline PTPases that showed significant homology with the predicted primary structures of PhoD from Zymomonas mobilis and PhoV from Synechococcus spp., although PTPase activities of PhoD and PhoV were not investigated (3).…”
mentioning
confidence: 99%
“…Moreover the identified peptide shares identity with several alkaline phosphatases in N. crassa and S. commune. It has been reported that alkaline phosphatase might dephosphorylate phosphotyrosyl proteins, 28) but it is known that alkaline phosphatase activity is completely inhibited by EDTA and is increased by Ca 2þ , Mg 2þ , and Co 2þ . [28][29][30][31] The fact that EDTA, Mg 2þ , Ca 2þ , and Co 2þ at concentrations from 0.5 mM to 20 mM did not affect dephosphorylation activity in our experiments disproves that the extracellular enzyme is an alkaline phosphatase.…”
Section: Discussionmentioning
confidence: 99%